Molecular epidemiology of extended-spectrum beta-lactamase-producing Escherichia coli in Tunisia and characterization of their virulence factors and plasmid addiction systems - Mnif, Basma (BioMed Central, 2013)
BACKGROUND: Extended-spectrum β-lactamases (ESBLs), particularly CTX-M- type ESBLs, are among the most important resistance determinants spreading worldwide in Enterobacteriaceae. The aim of this study was to characterize a collection of 163 ESBL-producing Escherichia coli collected in Tunisia, their ESBL-encoding plasmids and plasmid associated addiction systems. RESULTS: The collection comprised 163 ESBL producers collected from two university hospitals of Sfax between 1989 and 2009. 118 isolates harbored bla(CTX-M) gene (101 bla(CTX-M-15) gene and 17 bla(CTX-M-14) gene). 49 isolates carried bla(SHV-12) gene, 9 bla(SHV-2a) gene and only 3 bla(TEM-26) gene. 16 isolates produced both CTX-M and SHV-12. The 101 CTX-M-15-producing isolates were significantly associated to phylogroup B2 and exhibiting a high number of virulence factors. 24 (23.7%) of the group B2 isolates belonged to clonal complex ST131. Pulsed-field gel electrophoresis (PFGE) typing revealed a genetic diversity of the isolates. 144 ESBL determinants were transferable mostly by conjugation. The majority of plasmid carrying blaCTX-M-15 genes (72/88) were assigned to various single replicon or multireplicon IncF types and had significantly a higher frequency of addiction systems, notably the VagCD module. CONCLUSION: This study demonstrates that the dissemination of CTX-M-15 producing E. coli in our setting was due to the spread of various IncF-type plasmids harboring multiple addiction systems, into related clones with high frequency of virulence determinants.